Factors affecting bird fauna in patches of urban private forests in Southeastern Brazil - Campos-Silva, Lucas Andrei (2018)
Urban ecology has received attention in the recent scientific literature, but most studies are conducted in public areas. Many private closed gated communities have been created in Neotropical cities, often including patches of native vegetation. Fragments of native vegetation shelter a noteworthy urban biodiversity, and private areas could be managed together to public parks to offer friendly sites for urban avifauna. Yet, little is known about the importance of these private forests for bird conservation. Here we characterized the bird-fauna composition in patches of native private forests and analyzed the effects of a set of biological and environmental characteristics on birds. We performed this study in Sorocaba (Brazil) in 28 patches of private forests in 17 closed gated communities, from September 2016 to September 2017. We sampled bird fauna through 46 fixed-points counts (one to six per gated communities) and evaluated 16 environmental variables (14 local - vegetation structure - and two of the landscape) in plots of 10mx10m. We recorded 72 species of birds, mostly diet- and habitat specialists (58%). These private forests harbor many forest dependent/semi depend species (65% of all sampled species). Eight local variables have affected the species richness, diversity, abundance, trophic guilds, and forest dependence. Percentage of forest cover has influenced abundance, trophic guilds and forest dependence. Yet, patches of private native vegetation may be relevant refuges to urban birds, and proper management may enhance their role in maintaining a more specialized bird fauna.